Atmospheric CO2 as a resource for renewable energy production: A European energy law appraisal of direct air capture fuels. Issue 2 (18th February 2022) - Schaller, Romina; Markus, Till; Korte, Klaas; Gawel, Erik
Abstract: The high concentration of carbon dioxide (CO2 ) in the atmosphere is considered the root cause of climate change. However, in the future atmospheric CO2 could play a strategic role towards a renewable energy transition due to its use as a carbon source for the production of goods. Notably, direct air capture (DAC) technology, by removing CO2 from the atmosphere, could support and improve the carbon footprint of the transport and building sector, both of which are responsible for a large part of the world's greenhouse gas emissions. Once the CO2 is removed, it can be used to produce synthetic fuels for the transport sector, where there are few low‐carbon alternatives, such as aviation and shipping. In this article, we examine European Union legislation, focusing on the Renewable Energy Directive, and conclude that DAC fuels can be considered as renewable energy for the transport sector. Moreover, we highlight that the Directive does not yet regulate the methodology that defines the renewable character of DAC fuels and examine relevant criteria to be considered. In addition, because DAC can possibly be operated in buildings, we examine whether the Energy Performance of Buildings Directive is a legal instrument to be considered for deploying this technology.